Women and social reform in modern India : a reader - Sarkar, Sumit, 1939-; Sarkar, Tanika, 1949- (Bloomington : Indiana University Press, 2008)
Contributed articles on social reforms and status of women in 19th and 20th century India.
Keywords: Women -- India -- Social conditions -- 19th century; Women -- India -- Social conditions -- 20th century; Social problems -- India -- 19th century; Social problems -- India -- 20th century; Social change -- India -- 19th century; Social change -- India -- 20th century